A liquid immunogenic fiducial eluter for image-guided radiotherapy - Moreau, Michele; Richards, Geraud; Yasmin-Karim, Sayeda; Narang, Amol; Deville, Curtiland; Ngwa, Wilfred (Frontiers in Oncology, 2022)
Fiducials are routinely used to provide image-guidance during radiotherapy. Here, a new nanoparticle-based liquid immunogenic fiducial is investigated for its potential to provide image-guidance, while also enhancing treatment outcomes. This fiducial, liquid immunogenic fiducial eluter (LIFE) biomaterial, is formulated with natural biodegradable polymers, chitosan and sodium alginate with radio-sensitizing nanoparticles, and immunoadjuvant like anti-CD40 monoclonal antibody. Once administered intra-tumorally, this liquid smart radiotherapy biomaterial congeals within the calcium rich tumor microenvironment. The potential use of LIFE biomaterial for providing image guidance in magnetic resonance imaging (MRI) and computed tomography (CT) was investigated over different time period in a pre-clinical tumored mouse model. Results showed that the LIFE biomaterial can provide both MRI contrast and CT imaging contrast over 3-weeks, with gradual decrease of the contrast over time, as the LIFE biomaterial biodegrades. Results also showed the LIFE biomaterial significantly slowed tumor growth and prolonged mice survival (p < 0.0001) over time. The results highlight the potential use of the LIFE biomaterial as a multi-functional smart radiotherapy biomaterial that could be developed and optimized for hypo-fractionated radiotherapy applications and combining radiotherapy with immunoadjuvants.